Behaviour of Disc Oedema During and After Amiodarone Optic Neuropathy: Case Report - Martínez-LóPez-Portillo, Med. Alejandro (JCDR Research and Publications (P) Limited, 2014)
A 73-year-old woman with atrial fibrillation treated with Amiodarone presented with Optic Disc oedema in right eye (OD). Using Optical Coherence Tomography (OCT) we describe the impact of this neuropathy on Retinal Nerve Fibre Layer (RNFL). At diagnosis RNFL average was of 188 μm OD and 77 μm in the left eye (OS), six months after discontinuation of the drug decreased to 40 μm in OD and 76 μm in OS. The RNFL average of OD presented a transient increase during the acute oedema that returned to normal levels during the first month after discontinuation of the drug and fell dramatically to 44 μm at the second month and 40 μm at the sixth month. We show there is axonal loss after amiodarone-associated optic neuropathy measured with OCT. The OCT may be used in these patients to document changes in RNFL in the follow-up.